The Inter-American Court of Human Rights Advisory Opinion OC-23/17 on the Relationship between Human Rights and the Environment - Siwior, Przemysław (Review of European and Comparative Law, 2021)
On 15 November 2017, the Inter-American Court of Human Rights issued an advisory opinion OC-23/17 on the relationship between human rights and the environment. The opinion responded to a request made by Colombia pursuant to Article 64(1) of the American Convention on Human Rights regarding extraterritorial jurisdiction of state parties to the Convention resulting from mega-infrastructure projects in the Greater Caribbean region. The purpose of this article is to discuss the general issues dealt with by the Court, concentrating on the significance of this Advisory Opinion for international law. The opinion contains two main interesting aspects. First, in the light of the opinion, states are responsible for the environmental damage they cause, regardless of whether it occurs within their borders or beyond them. Second, the Advisory Opinion recognizes that the right to a healthy environment is an autonomous, fundamental human right that shall be protected.